Prognostic and Clinicopathological Significance of Hypoxia-Inducible Factor-1α in Endometrial Cancer: A Meta-Analysis - Zhu, Ping; Shen, Longxia; Ren, Qiuxia; Zeng, Qingxiang; He, Xiaocui (Frontiers in Oncology, 2020)
Background: Current reports on the prognostic and predictive value of hypoxia-inducible factor-1α (HIF-1α) in endometrial carcinoma are inconsistent. Therefore, we conducted this meta-analysis to precisely evaluate the association of HIF-1α expression with susceptibility, clinical features, and prognosis of endometrial cancer. Methods: Eligible studies which assessed the role of HIF-1α protein expression, immunohistochemistry detection, disease susceptibility, clinical features, and prognosis of endometrial cancer were searched from the Embase, Pubmed, and Web of Science databases. Stata 14.0 software was used to merge and compute pooled hazard ratios (HR) and odds ratios (OR). Information including HIF-1α protein expression and clinical progression of endometrial cancer was extracted. The pooled HR and OR with corresponding 95% confidence intervals (CI) were used to estimate the strength of these associations. Results: A total of 25 studies were included in the analysis. HIF-1α protein expression in endometrial cancer tissue was significantly higher than that in normal tissues (OR = 15.79, 95% CI = 8.44–29.52, P < 0.05). Endometrial cancer patients with higher HIF-1α protein expression had poorer prognosis compared to patients with low HIF-1α protein expression (HR = 2.29, 95% CI = 1.68–2.90, P < 0.05). In addition, high HIF-1α protein expression was significantly associated with endometrial cancer grade, lymph node metastasis, and myometrial invasion (Grade in Caucasians: OR = 3.09, 95% CI = 1.63–5.85, P < 0.05; Lymph node metastasis: OR = 3.09, 95% CI = 1.63–5.85, P < 0.05; Myometrial invasion: OR = 2.26, 95% CI = 2.15–5.08, P < 0.05). Conclusions: HIF-1α overexpression was significantly associated with increased risk, advanced clinical progression, and poor prognosis in endometrial cancer patients.